Experiences of nursing students during their mental health clinical training at a general hospital in Namibia - Daniel O. Ashipala; Daniel Mbishi; Louise Pretorius (AOSIS, 2023)
Background: Clinical training is important because it constitutes more than half of the formal courses in nursing education. Accordingly, it is important for institutions of higher learning to continually explore the experiences of nursing students during their clinical placement. These experiences can be used to promote a positive clinical learning environment for students. However, the experiences of nursing students during their mental health clinical training in Namibia have not been extensively researched. Objectives: The aim of this study was to explore and describe the experiences of nursing students during their mental health clinical training at a general hospital in Namibia. Method: A qualitative, exploratory, descriptive and contextual research design was followed as the basis for conducting the study. A sample of 15 nursing students was conveniently selected from the target population of 73 nursing students. This sample size was determined by the saturation of data as reflected in repeating themes. Results: The following three themes emerged: collating theory and mental health practice experiences, facing challenges in clinical placements, and recommendations to ensure effective learning about mental health. Conclusion: The use of a general hospital for clinical placements within an undergraduate nurse training course led to some concerns regarding the relevance and appropriateness of such experience within a nursing programme. Contribution: The findings have important implications for the training of undergraduate nursing students in general hospitals. It can be utilised to develop strategies to improve positive clinical practice placement and develop clinical skills for undergraduate nursing students in general hospitals.